3D-assembled Ag nanowires for use in plasmon-enhanced spectroscopic sensors. Issue 4 (21st April 2019) - Park, Sung-Gyu; Kang, Mijeong; Kim, Sunho; Jung, Ho Sang; Kim, Dong-Ho
ABSTRACT: Surface plasmon-enhanced spectroscopic sensors for fluorescence and Raman spectroscopy use high-density metallic nanostructures to strongly enhance the light–matter interaction. In this contribution, we will review the processes by which three-dimensional (3D) multilayered Ag nanowires assemble from one-dimensional Ag nanowires and their plasmon-enhanced sensing applications, giving emphasis to the physical mechanism underlying the plasmon-enhanced spectroscopy. In particular, we discuss the practical aspects of 3D porous and flexible plasmonic platforms used for spectroscopic sensing applications. Combining a portable spectrometer with a low-cost but highly sensitive and flexible plasmonic substrate is potentially useful for on-site chemical analysis in the contexts of environmental monitoring, food safety, forensic science, and point-of-care healthcare medical diagnostics.